Epidemiological aspects of dengue in the State of Mato Grosso, Brazil: time series between the years 2001 and 2018 (Research, Society and Development, 2021)
Objective: To describe the epidemiological characteristics of dengue in the State of Mato Grosso, Brazil, from 2001 to 2018.Methods: Data were obtained from the Informatics Department of the Unified Health System (DATASUS) for analyzes of lethality, incidence and hospitalization. Results: In the state of  Mato Grosso there were 292,756 notifications and 256 deaths in the period studied. The peak of incidence and lethality was in 2009 (male 1544.1; female 1960.3; male 268.1; female 107.2 cases / 100 thousand inhabitants), respectively. However, the hospital admission rate (male 156.4 / 100 thousand inhabitants; female 178.1 / 100 thousand inhabitants) was in 2010. The peak incidence rate in the age groups was in 2009, in which children ( 60 years; 1257.1 / 100 thousand inhabitants). The highest lethality rate was in the elderly 435.9 / 100 thousand inhabitants, then in children (